(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The information in this article is a food safety system standard developed in detail by food manufacturers, retailers, food service providers, and food industry professionals. This standard was first published by the BRC - the British Retail Consortium in 1998 and has been updated seven times to date. The BRC food safety system provides the basis for managing operational management in the production, processing and packaging of food products to ensure food safety, integrity, legitimacy and quality.